A PSICOTERAPIA BREVE OPERACIONALIZADA DE MULHERES EM SITUAÇÃO DE VIOLÊNCIA DOMÉSTICA - Nukui, Sonia Maria Machado de Oliveira (2012)
This research was conducted with two women under situations of domestic violence and was based on theoretical, technical and methodological aspects of psychological intervention called OBP-Operational Brief Psychotherapy. The aim was to analyze the process of OBP of women in situations of domestic violence. The method was a clinical study of the psychoanalytic approach that is based on the study of descriptive case study. Participants performed five diagnostic interviews and were also classified with severe ineffective adaptation featuring most limiting neurotic symptoms, inhibitions and restrictive rigidity of character traits. They went through OBP and after the end of the process the Follow up interviews were reassessed by EDAO. The data that was obtained in follow-up interviews showed that there was a change in adaptive efficiency. Participants were also classified with Moderate Inefficient Adaptation. They had some neurotic symptoms, moderate inhibition, some character traits. Our conclusion is that in the studied cases, though the analysis by sectors, the affective relational sector has established itself as a source of conflict and dissatisfaction bringing very few appropriate solutions, decisively influencing other sectors of adaptation. In addition, we observed the phenomenon of reproduction models of the past in the established relations in the present. In both studied cases there was a situation of physical and sexual abuse, which was configured as an inheritance coming from a relational dynamic of the family of origin and perpetuated freely in their nuclear families. Finally, it should be noticed that the patients participated actively during the therapeutic process. From the theorized interpretations, they were able to reconsider their attitudes towards problematic situations experienced and they were able to take some concrete steps to deal with them more adequately during and after the psychotherapeutic process. It was found that the process of brief psychotherapy and the use of operationalized theorized interpretations seem to have contributed to the change in the quality of adaptive efficacy of two women who took part in this study.